2021
DOI: 10.9734/jpri/2021/v33i30a31625
|View full text |Cite
|
Sign up to set email alerts
|

Androgenetic Alopecia as a Marker of Metabolic Syndrome

Abstract: Background: Alopecia induced by androgens in genetically predisposed individuals is termed as Androgenetic alopecia (AGA). There is proof appearance the relationship between Androgenetic alopecia and metabolic condition. Objective: To determine frequency of metabolic syndrome in Androgenetic alopecia as a biomarker of disease in adult male patients. Materials and methods: It was a Cross Sectional Study conducted at the Department of Dermatology, Liaquat University of Medical and Health Sciences Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…It is a complex metabolic syndrome and a risk factor for diabetic cardiovascular and cerebrovascular diseases. Over the past two decades, the relationship between AGA and MetS has been proven [ 53 ]. In a case and control study involving 100 AGA cases (20–50 years), MetS were observed in 53% of cases and 17% of controls ( P = 0.001) [ 54 ].…”
Section: Metabolic Diseasementioning
confidence: 99%
“…It is a complex metabolic syndrome and a risk factor for diabetic cardiovascular and cerebrovascular diseases. Over the past two decades, the relationship between AGA and MetS has been proven [ 53 ]. In a case and control study involving 100 AGA cases (20–50 years), MetS were observed in 53% of cases and 17% of controls ( P = 0.001) [ 54 ].…”
Section: Metabolic Diseasementioning
confidence: 99%
“…The occurrence and development of AGA are often accompanied by a disruption in the balance of one of the body's (especially androgenic) metabolic functions, and as such, it may be more than just a simple skin condition, but may also serve as an early warning sign of an underlying systemic disease. such as prostate cancer (Babaei et al, 2021; Liang et al, 2018), metabolic syndrome (Gopinath & Upadya, 2016; Memon et al, 2021), seborrheic dermatitis, autoimmune defects (Castano Castrillon et al, 2019; Krysiak et al, 2021), and certain psychological disorders (Huang et al, 2021; Tabolli et al, 2013; Tas et al, 2018). Thereby, there is an urgent need to find a safe and effective anti‐AGA drug, and mining safe and efficient natural bioactive compounds from Chinese herbal medicine is an effective way to screen anti‐AGA drugs (Dou et al, 2022).…”
Section: Introductionmentioning
confidence: 99%